2019
DOI: 10.1109/access.2019.2948656
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Analysis of Two-Way Relay Networks: A Joint Mechanism Using NOMA and Network Coding

Abstract: As a promising technology, non-orthogonal multiple access (NOMA) enhances spectral efficiency and system capacity by allocating the same resource to multiple users. Network coding (NC) has the advantages of compressing data and high spectral efficiency, and it plays a crucial role in two-way relay networks. However, conventional two-way relay networks suffer from throughput limitations due to the use of OMA scheme. In this paper, we utilize a hybrid concept to design a two-way relaying system (namely Hybrid-TW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Considering cognitive radio NOMA (CR-NOMA) networks, they introduced a two-way full-duplex (TW-FD) relaying to achieve better energy efficiency since the selfinterference (SI) of FD can be regarded as a potential source related to harvest energy. Their main results indicated maximal security energy efficiency can be obtained for the secondary user (SU) system [21]. Other investigations as in [22] and [23] showed the advantages of FD TWR-CNOMA systems.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Considering cognitive radio NOMA (CR-NOMA) networks, they introduced a two-way full-duplex (TW-FD) relaying to achieve better energy efficiency since the selfinterference (SI) of FD can be regarded as a potential source related to harvest energy. Their main results indicated maximal security energy efficiency can be obtained for the secondary user (SU) system [21]. Other investigations as in [22] and [23] showed the advantages of FD TWR-CNOMA systems.…”
Section: Introductionmentioning
confidence: 95%
“…They showed that its performance is better than a conventional one way CNOMA system in terms of outage probability and ergodic rate. With characterizations of compressing data and high spectral efficiency in Network Coding (NC), the authors in [21] introduced a hybrid concept to employ a two-way relaying system (namely Hybrid-TWRS) which combines NOMA and NC.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the realistic assumptions of the residual hardware impairments or ipCSIs of two-way or multiway CNOMA networks have also been considered in the articles [21,22,30]. Moreover, DNC and NOMA techniques can be combined to decreasing transmission time between devices and improve the performance system [5,31,32]. In [31,32], the authors combined NOMA and DNC techniques in a twoway DF relay cooperative scheme confirming that performance in this proposed asymmetric scheme had better spectrum utilization efficiency than the traditional two-way DF OMA scheme, the two-way DF with only using the CNOMA, and the two-way relaying system with OMA in the uplink and DNC in the downlink.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, DNC and NOMA techniques can be combined to decreasing transmission time between devices and improve the performance system [5,31,32]. In [31,32], the authors combined NOMA and DNC techniques in a twoway DF relay cooperative scheme confirming that performance in this proposed asymmetric scheme had better spectrum utilization efficiency than the traditional two-way DF OMA scheme, the two-way DF with only using the CNOMA, and the two-way relaying system with OMA in the uplink and DNC in the downlink. The authors in [31,32] only used [31] was considered in the case of the ideal conditions.…”
Section: Related Workmentioning
confidence: 99%
“…firstly decodes received signal and then re-transmits decoded signal to the destination. Lately, various works on the performance of cooperative relay network combined with the NOMA scheme have appeared in the literature [9]- [14]. Spatial multiplexing in cooperative relay network combined with the NOMA is presented in [15] to improve the spectral efficiency.…”
Section: Introductionmentioning
confidence: 99%